Global research on the crosstalk between intestinal microbiome and colorectal cancer: A visualization analysis - Yang, Shanshan; Hao, Shaodong; Ye, Hui; Zhang, Xuezhi (Frontiers in Cellular and Infection Microbiology, 2023)
Background: There is increasing evidence showing intestinal microbiome (IM) is highly linked to colorectal cancer (CRC). To investigate scientific output, identify high-cited papers, and explore the research hotspots and trends in the field of IM/CRC, we conducted a bibliometric and visualized analysis. Methods: A bibliographic search regarding IM/CRC research (2012-2021) was implemented on October 17, 2022. The terms attached to IM and CRC were searched in the titles (TI), abstracts (AB), and author keywords (AK). The main information was extracted from the Web of Science Core Collection (WoSCC). The Biblioshiny from R packages and VOSviewer were used for data visualization. Results: There were 1725 papers related to IM/CRC retrieved. The number of papers (Np) in IM/CRC is growing rapidly from 2012 to 2021 (especially after 2018). China and the United States were in the leading position and made the most contributions to IM/CRC. Shanghai Jiao Tong University and Harvard University had the maximum Np. The most productive authors were Yu Jun and Fang Jing-Yuan. International Journal of Molecular Sciences received the most Np, while Gut had the most citations. The historical development of IM/CRC was demonstrated through historical citation analysis. The current status and hotpots were highlighted through high-cited publications and cluster analysis of common keywords. The hot topics included the effect of GM on tumorigenesis, the effect of GM treatment of CRC, the role of GM in CRC screening, the mechanisms of GM involved in CRC, and GM modulation for CRC management. Some topics such as "chemotherapy", "immunotherapy", "Fusobacterium nucleatum”, “short-chain fatty acids" and "biomarkers" could be the focus of IM/CRC research in the coming years. Conclusion: This research evaluated global scientific output on IM/CRC research and its quantitative features, identified some key papers, and gathered information on the status and trends of IM/CRC research, which may shape future paths for academics and practitioners.